Effect of PMSG administration in combination with vaginal sponge on estrous occurrence and litter size of Javanese sheep - Rangga Setiawan; Siti Darodjah Rasad; Nurcholidah Solihati; Rini Widyastuti; Soeparna Soeparna (Universitas Syiah Kuala, 2017)
AbstractThe use of vaginal sponge in estrous synchronization has been a popular method to uniform estrous cycle of small ruminants. In order to increase the litter size, the use of the sponge is combined with PMSG. Therefore the objective of this study was to evaluate the effect of PMSG in combination with vaginal sponge on estrous response and litter size of Javanese local sheep. The study was conducted in Faculty of Animal Husbandry, Padjadjaran University, Indonesia with 32 non-pregnant local sheep. All these sheep was divided into four groups of treatment, i.e: 1) group of sheep was subjected to vaginal sponge (VS) treatment containing 30 mg Medroxyprogesterone acetat (MAP) inserted in the vagina for 14 days; 2) group of sheep was subjected to the 30 mg MAP in VS plus 300 IU PMSG injection -1 d before VS removal; 3) group of sheep was subjected to the 30 mg MAP in VS plus 300 IU PMSG injection at the day of VS removal; 4) group of sheep was subjected to the 30 mg MAP in VS plus 300 IU PMSG injection +1 d after VS removal. The result showed that all treatment groups had 100% of estrous response. However, the occurrence of estrous time varied among group after VS removal. Group 1 (G1) and G4 tend to have estrous occurrence at day 3 after VS removal by 55% and 75% response, respectively. Whilst, G2 and G3 tend to have estrous occurrence respectively at day 1 (62,5%) and day 2 (50%) after VS removal. A 100% of pregnancy rate occurs in G2 and G4, while G1 and G3 have a 88,9% and 87,5%, respectively. No significant effects of the treatments on the ewes litter size. In conclusion, the use of PMSG administration 24 h prior, after, or at sponge withdrawal increase a tighter synchrony of oestrous and pregnancy rate, but has no effect on the increasing of litter size in Javanese local sheep.Keywords: Vaginal sponge, PMSG, estrous response, pregnancy rate, litter size, sheep